Associations Between Anabolic-Androgenic Steroid Use and Sexual Health Behaviors Among Adolescent Boys: Results From the 2019 Youth Risk Behavior Survey. Issue 4 (August 2022) - Ganson, Kyle T.; Jackson, Dylan B.; Testa, Alexander; Murnane, Pamela M.; Nagata, Jason M.
The aim of this study was to determine the association between lifetime anabolic-androgenic steroid (AAS) use and seven indicators of sexual health behaviors among a nationally representative sample of adolescent boys in the United States. Multiple modified Poisson regression analyses were conducted to determine the associations between any lifetime AAS use and seven indicators of sexual health behaviors among 2, 095 sexually active adolescent boys from the 2019 National Youth Risk Behavior Survey. Sexually active boys who reported lifetime AAS use were at greater risk of having sexual intercourse before the age of 13 years (adjusted risk ratio [aRR] = 2.73, 95% confidence interval [CI] = [1.44, 5.17]), reporting ≥4 sexual partners in their lifetime (aRR = 1.96, 95% CI = [1.34, 2.89]) and in the past 3 months (aRR = 6.77, 95% CI = [3.19, 14.37]), having been tested for HIV in their lifetime (aRR = 2.49, 95% CI = [1.13, 4.73]), and having been tested for any sexually transmitted infection in the past 12 months (aRR = 3.14, 95% CI = [1.63, 6.03]). These findings align with prior research among adult men and have implications for public health and health care prevention efforts to reduce the use of AAS, as well as support the engagement in safe sexual health behaviors among adolescent boys.